Direct Evidence of Two-component Ejecta in Supernova 2016gkg from Nebular Spectroscopy - Kuncarayakti, Hanindyo (2020)
Spectral observations of the type-IIb supernova (SN) 2016gkg at 300-800 days are reported. The spectra show nebular characteristics, revealing emission from the progenitor star´s metal-rich core and providing clues to the kinematics and physical conditions of the explosion. The nebular spectra are dominated by emission lines of [O i] λλ6300, 6364 and [Ca ii] λλ7292, 7324. Other notable, albeit weaker, emission lines include Mg I] λ4571, [Fe ii] λ7155, O I λ7774, Ca II triplet, and a broad, boxy feature at the location of Hα. Unlike in other stripped-envelope SNe, the [O i] doublet is clearly resolved due to the presence of strong narrow components. The doublet shows an unprecedented emission line profile consisting of at least three components for each [O i]λ6300, 6364 line: a broad component (width ∼2000 km s-1), and a pair of narrow blue and red components (width ∼300 km s-1) mirrored against the rest velocity. The narrow component appears also in other lines, and is conspicuous in [O i]. This indicates the presence of multiple distinct kinematic components of material at low and high velocities. The low-velocity components are likely to be produced by a dense, slow-moving emitting region near the center, while the broad components are emitted over a larger volume. These observations suggest an asymmetric explosion, supporting the idea of two-component ejecta that influence the resulting late-time spectra and light curves. SN 2016gkg thus presents striking evidence for significant asymmetry in a standard-energy SN explosion. The presence of material at low velocity, which is not predicted in 1D simulations, emphasizes the importance of multidimensional explosion modeling of SNe.